Dysregulated Retinoic Acid Signaling in the Pathogenesis of Pseudoexfoliation Syndrome - Zenkel, Matthias; Hoja, Ursula; Gießl, Andreas; Berner, Daniel; Hohberger, Bettina; Weller, Julia; König, Loretta; Huebner, Lisa; Ostermann, Thomas A.; Gusek-Schneider, Gabriele; Kruse, Friedrich; Pasutto, Francesca; et al. (International Journal of Molecular Sciences, 2022)
Pseudoexfoliation (PEX) syndrome, a stress-induced fibrotic matrix process, is the most common recognizable cause of open-angle glaucoma worldwide. The recent identification of PEX-associated gene variants uncovered the vitamin A metabolic pathway as a factor influencing the risk of disease. In this study, we analyzed the role of the retinoic acid (RA) signaling pathway in the PEX-associated matrix metabolism and evaluated its targeting as a potential candidate for an anti-fibrotic intervention. We provided evidence that decreased expression levels of RA pathway components and diminished RA signaling activity occur in an antagonistic crosstalk with TGF-beta 1/Smad signaling in ocular tissues and cells from PEX patients when compared with age-matched controls. Genetic and pharmacologic modes of RA pathway inhibition induced the expression and production of PEX-associated matrix components by disease-relevant cell culture models in vitro. Conversely, RA signaling pathway activation by natural and synthetic retinoids was able to suppress PEX-associated matrix production and formation of microfibrillar networks via antagonization of Smad-dependent TGF-beta 1 signaling. The findings indicate that deficient RA signaling in conjunction with hyperactivated TGF-beta 1 /Smad signaling is a driver of PEX-associated fibrosis, and that restoration of RA signaling may be a promising strategy for anti-fibrotic intervention in patients with PEX syndrome and glaucoma.
CRIS-Team WoS Importer:2022-06-24
Keywords: pseudoexfoliation syndrome; pseudoexfoliation glaucoma; retinol; retinoic acid; extracellular matrix; fibrosis; TGF-β1